Namūżaju Ikhtibār Mufradāt al-Lugah al-‘Arabiyyah wa Taqyīmuhā - Mahmudi, Ihwan; Wulandari, Dina ayu; Rahmawati, Zakiya Setyo (Study Program of Arabic Language Teaching, 2023)
Arabic language teaching in Indonesia has different levels of difficulty. Learning Arabic starts from simple vocabulary and is one of the areas of Arabic language teaching. Vocabulary is an important part of students' linguistic competence. Tests are an important part of the teacher's job. Tests have many purposes that cannot be ignored by students, teachers, parents, schools or universities. An example in the field of learning is to measure competence.The objectives of this study are: first, to know the vocabulary test module in Arabic learning, second to know the purpose of vocabulary test in Arabic learning, and third to know how to evaluate vocabulary test in Arabic learning. This type of research is qualitative and descriptive research with the classification of the test according to the mufradat lesson. This study found 11 examples in the test as in the language test book. And the ways to evaluate these tests in this way can be found ways of evaluation in making questions on mufradat lessons in Arabic.